2015
DOI: 10.4137/cmrh.s25494
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Culture System Using the INVOcell Device Shows Similar Pregnancy and Implantation Rates to those Obtained from in Vivo Culture System in ICSI Procedures

Abstract: CAPSULEClinical outcomes using INVOcell device with ICSI.OBJECTIVEIntravaginal culture of oocytes (INVO) procedure is an intravaginal culture system that utilizes the INVOcell device in which the fertilization and embryo culture occur. In this procedure, the vaginal cavity serves as an incubator for oocyte fertilization and early embryonic development. The objective of this study was to evaluate the clinical outcomes of this intravaginal culture system in intracytoplasmic sperm injection (ICSI).METHODSA total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…A second nonrandomized trial of 24 patients resulted in 13 clinical pregnancies. This was similar to an internal matched IVF/ ICSI control group of 74 cycles, which generated a pregnancy rate 58% (60).…”
Section: Vaginal Incubation Of Eggs and Embryossupporting
confidence: 77%
“…A second nonrandomized trial of 24 patients resulted in 13 clinical pregnancies. This was similar to an internal matched IVF/ ICSI control group of 74 cycles, which generated a pregnancy rate 58% (60).…”
Section: Vaginal Incubation Of Eggs and Embryossupporting
confidence: 77%
“…The second prospective non-randomized study found that IVC/ICSI produced a cleavage rate of 79 % and a live birth rate of 53 %. This was found similar to an internal matched IVF/ICSI control group of 74 cycles, which generated a cleavage rate of 76 % and a live birth rate 58 % [11]. The third study examined sister oocytes from 10 women who were randomized to receive either IVC or IVF.…”
Section: Introductionmentioning
confidence: 56%
“…, 2012 ). García-Ferreyra etal. (2015) used ICSI embryos and found comparable Day 3 development and PRs.…”
Section: Resultsmentioning
confidence: 99%